REDUÇÃO DA QUALIDADE ADSORTIVA DE CARVÕES ATIVADOS INDUZIDA POR ATIVIDADE MICROBIOLÓGICA - ARAUJO, JEAN CANTON DE (2022)
The wetting of pulverized activated carbons is relatively recent in the coal industry and came with the objective of reducing the dispersion of this material, however this process brought inconveniences such as an environment conducive to microbial proliferation, this growth can lead to contamination of the industrial processes and the loss of the adsorpitive capacity when stored for long time periods. Taking this in consideration, this study aims studying how physically and chemically activated carbon, of dry and wetted base, are affected by the time of storage and by the microbial growth. Nine samples were used in the study, being three of dry base with the acronym of (AQA) Ativado quimicamente ácido, (AFA) Ativado fisicamente ácido, (AFB) Ativado fisicamente e básico, and its respective ummected forms (AFAU, AFAU-d, AFBU, AFBU-d, AQAU e AQAU-d), U standing for Ummected and -d standing for wetting with deionezed water. For microbial monitoring, it was used surface plating with aerobic mesophyll count obtained by suspention and extracted by sonication, besides molds and yeast analysis for AQA umected carbons. For characterization analyses of the carbons were applied Boehm's titrations, infrared spectroscopy and elementary analysis, for monitoring of the physicochemical properties were applied moisture analysis, zero charge point (pHz), potential zeta, water activity (aw) and iodine index. Physically activated carbons presented higher counts of colonies than chemically activated carbons, and for the wet samples AQA e AFB, the wetting with deionizes water led to a lower microbial activity. Physically activated carbons had higher CFU counts, with the number of colonies ranging from 104 -107 CFU/g, while chemically activated carbons had counts ranging from 103 -105 CFU/g. For AQA, AFA and AFB dry-based coals, the limit moisture content for the appearance of colonies was 27%, 17.5% and 18.3%, respectively. Due to the higher degree of hydrophilicity, chemically activated carbons presented lower water activity (Aa) values than physically activated carbons, and the absence of electrolytes led to higher Aa values for carbons wetted with deionized water when compared to treated water. The iodine index analyzes showed a decrease in the available adsorption surface caused by microorganisms, mainly for chemically activated carbons, which lost 85 mg/g of iodine index and presented microorganisms with fungal morphology and filamentous nature, being possible to observe structures such as hyphae and mycelia in microscope. The study showed that there is a loss of adsorptive capacity caused by the proliferation of microorganisms, both for dry and wet samples.